The integration of Chinese traditional instruments in contemporary symphony ensembles - Huang, Jiahui; Huang, Jiayao (Música Hodie, 2025)
The aim of the work was to reveal the nature of the aesthetic and functional interaction of Chinese instruments with the academic orchestral tradition in the context of the globalised musical space. The research used a comprehensive methodological approach that combined historical and cultural analysis, comparative aesthetic reconstruction, structural and functional generalisation of orchestral practice, and musicological study of scores and audiovisual sources. The material was based on works by contemporary composers in which Chinese instruments (erhu, pipa, sheng, xun, percussion) were integrated into the symphonic texture in various formats. As a result, it was found that traditional Chinese instruments had a multifunctional load formed in the context of historical, social and philosophical traditions. It was found that a modern symphony orchestra is capable of flexible adaptation and expansion of the timbre palette through the integration of non-European instruments. Three main models of incorporating Chinese instruments into the orchestral context have been identified: as a soloistic form, as a textural component, and as a functional substitute. Each of the models was accompanied by specific challenges – technical, timbre and dramatic – that required adaptation on the part of composers and conductors. The musicological analysis of the works has demonstrated that Chinese instruments not only complemented the orchestral palette, but also transformed the compositional logic, introducing new semantic and cultural codes into the symphonic discourse. The practical significance of the research results lies in the possibility of applying the typology of integration models in composing and performing practice, as well as in the development of intercultural music education and orchestral drama in the context of global artistic dialogue.